PENGARUH KESADARAN WAJIB PAJAK, PENGETAHUAN PERPAJAKAN, DAN PERSEPSI EFEKTIVITAS SISTEM PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK - Nurul Rachmania Arlianti (2022)
This study was conducted to examine the effect of the variabels of taxpayer awareness, tax knowladge, and perceptions of the effectiveness of the taxation system on taxpayer compliance among employees in DKI Jakarta. The independent variables used in this study are taxpayer awareness, tax knowledge, and perceptions of the effectiveness of the tax system. The dependent variable used in this study is taxpayer compliance. Determination of the sample using accidental sampling technique with the criteria of respondents used in this study, namely individual taxpayers who work in DKI Jakarta and have a NPWP. Accidental sampling is a technique that determines a sample by chance, and the sample is suitable to be used as a data source. The sample used in this research is 161 individual taxpayers who work in DKI Jakarta. Hypothesis testing using multiple linear regression with the help of SPSS version 26. The test results show that there is a significant positive effect between all independent variables, namely taxpayer awareness, tax knowledge, and perceptions of the effectiveness of the taxation system on the dependent variable of taxpayer compliance.